An in situ and ex situ study of χ phase formation in a hypoeutectic Fe-based hardfacing alloy. (March 2020) - Wieczerzak, K.; Michler, J.; Wheeler, J.M.; Lech, S.; Chulist, R.; Gondek, Ł.; Czub, J.; Hoser, A.; Schell, N.; Bała, P.
Abstract: In this work, the effect of topologically close-packed χ phase on the microstructure and properties of the rapidly solidified hypoeutectic iron-based Fe-25Cr-7Mo-0.8C alloy was investigated. The novelty of the work is based on the introduction of χ phase into the Fe-based hypoeutectic alloy with the aim of reducing the mean free path of the matrix and increasing abrasive resistance. The phase composition was studied using in situ neutron and ex situ X-ray synchrotron diffraction. The microstructural evolution was analyzed via scanning and transmission electron microscopy and modelled using CALPHAD thermodynamic calculations. The mechanical behavior of the evolving microstructure was quantified using high-speed nanoindentation mapping. At low temperatures (650 °C), the χ phase nucleates mainly in dendrite areas and exhibits a needle-like morphology caused by high misfit with the ferritic matrix. At higher temperatures (800 °C), the χ phase nucleates on carbide/matrix interfaces and in dendrites and is characterized by a blocky morphology. Simultaneously, the evolution of M23 C6 carbide morphology towards a continuous and solid network of precipitates was observed. Such changes in the alloy's microstructure induced an increase in hardness of about 16% and resulted in the reduction of the average scratch depth in comparison to as-cast state. Graphical abstract: Unlabelled Image Highlights: Formation of the χ phase in the Fe-25Cr-7Mo-0.8C alloy was established. Phase and microstructural evolution of the alloy was determined. Annealing temperature has a significant effect on the χ phase morphology. Annealing temperature affects the χ phase nucleation sites. The χ phase is beneficial for hardness and wear resistance enhancement.